Isolasi dan Karakterisasi Fungi Endofit Tanaman Tapak Dara (Catharanthus Roseus) - M. Arifuddin; Mahfuzun Bone; Iswahyudi Iswahyudi; Arsyik Ibrahim; Laode Rijai (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2017)
This study aims to determine the diversity of endophytic fungi Tread Dara (Catharanthus roseus) as one of the potential plants that can produce medicinal efficacious compounds. This study includes the isolation and identification of endophytic fungi on Tapak Dara plant using PDA medium. Based on the results obtained 6 endophytic fungal isolates originating from roots and leaves Tread Dara.